Historicising the emergence of the Aegean culture (1890s) - Fotiadis, Michael (Journal of Greek Archaeology, 2022)
In the course of the 20th century Aegean prehistory grew to a vigorous sub-discipline of archaeology and, in the process, the Aegean became firmly established as a distinct prehistoric culture. The notion of an Aegean culture hardened with time to the point that it is difficult today to reflect on its historicity. It is difficult, that is, to think of the Aegean concept as having arisen in a modern context, much easier to think of the Aegean culture as having existed since prehistory, waiting to be discovered by archaeology in the late 19th century. In this essay I try to negotiate the difficulties. More specifically, I review the historical conditions in which, and the processes by which, the Aegean emerged as a distinct prehistoric culture in the 1890s. In brief, I historicise the emergence of the Aegean culture. Historicising disciplinary concepts is a critical exercise. One needs to bring to the fore and scrutinise long-forgotten or overlooked details (e.g., premises of another era that were subsequently repudiated and were with time lost to memory). But make no mistake: historicising disciplinary concepts is heeding the fact that, like all things human, our concepts have histories; it is by no means tantamount to undermining or debunking the concepts under consideration. I will have a little more to say about this and a few other matters at the end of the essay.